Geotechnical assessment of terrain strength properties on Mars using the Perseverance rover's abrading bit. (June 2023) - Marteau, Eloïse; Wehage, Kristopher; Higa, Shoya; Moreland, Scott; Meirion-Griffith, Gareth
Highlights: To date, geotechnical instrumentation has been absent from Mars missions. The Perseverance rover's abrading bit has a similar form factor to a Bevameter. We study the use of the abrading bit tool to perform soil strength measurements. Abstract: An instrument for measuring the geotechnical properties of the Martian soil provides high-value science opportunities and high-priority mission-support capabilities that serve reconnaissance, science, and engineering. Such instrument can be used to characterize the terrain for drilling, landing, trafficability, and other surface operations. However, to date, instruments for measuring geotechnical properties have been absent from Mars exploration missions. This paper examines the use of the Mars 2020 Perseverance rover's abrading bit tool to perform regolith strength measurements. The Perseverance rover's abrading bit has a similar form factor to a Bevameter, a tool commonly used to collect engineering geotechnical data to assess terrain traversability. To demonstrate a methodology by which the abrading bit can be employed to characterize soil strength, a portable testbed that mimics the flight system is designed and built using commercial off-the-shelf components. A data-processing pipeline is developed to convert raw measurements to soil strength. Tests were performed on three characterized simulants with different mechanical properties. The results show that the abrading bit is capable of making shear and bearing strength measurements with quantified uncertainties and demonstrate, for the first time, the ability to perform controlled geotechnical analysis using a standard science instrument.